Characterization and assessment of naturally mutant non-pathogenic O27 strain Escherichia coli and their potential use as poultry probiotics (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The purpose of the current study was to evaluate the molecular characteristics of naturally mutant non-pathogenic O27 strain of Escherichia coli and its efficacy as probiotic in broilers and determine the best age at which it can be administered.  Materials and methods: A total of 24 virulence genes using 24 sets of primers were detected using the polymerase chain reaction technique. For probiotics experiments, 60 chicks (day 1 old) were divided into three groups, 20 per group, and reared for 4 weeks. The first group was considered as a negative control. The second group was treated orally with O27 strain at first day of life for three successive days and repeated at day 21. The third group was administered orally with O27 strain at day 10 old, and repeated at day 21 old.  Results: The data revealed that type 1 fimbrial adhesion, salmochelin siderophore receptor, and sigma factor-binding protein were detected in O27 strain, but temperature-sensitive hemagglutinin, hemolysin secretion gene, pyelonephritis-associated Pili gene, polysaccharide capsule synthesis gene, Shiga-toxin1 gene, Shiga-toxin2 gene, Brain microvascular endothelial cell invasion, E. coli attaching and effacing gene, heat-stable enterotoxin, heat-labile enterotoxin, east 1 toxin, colicin V, verotoxin type 2, necrotizing cytotoxic factor type 1, colonization factor antigen I, colonization factor antigen III, coli surface 2, coli surface 4, serine protease pic autransporter, vacuolating autotransporter toxin, and serine protease EspP precursor were not detected in O27 strain. Group 2 performance parameters were significantly better (p < 0.01) than groups 3 and 1. Hematological and biochemical parameters did not be influenced (p > 0.05) by the administration of O27 strain. Antibody titers of infectious bursal disease virus and Newcastle disease virus in groups 2 and 3 were improved as compared to group 1. Group 2 had significantly higher titers than group 3. Histopathologically, all groups showed normal histopathological pictures. However, jejunum in groups 2 and 3 showed more tall, intact, and densely packed microvilli and more crypt depth than the control group.  Conclusion: The O27 strain of E. coli is non-pathogenic bacteria. Its effects on growth performances and enhancement of immunity in broilers match with the same impact of probiotics, and these candidates will fit to be a good probiotic in the future. The results revealed that the effects of O27 strain at the day 1 old of life for three successive days and repeated at day 21 old are better for improving the performance and immunity of the birds. More research works about the characterized non-pathogenic E. coli strain O27 are required for field and commercial use.J. Adv. Vet. Anim. Res., 7(3): 374-383, Sep 2020http://doi.org/10.5455/javar.2020.g431